Advanced visualization using Gephi for financial network - Bahaludin, Hafizah (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia., 2022)
The financial network based on the correlation network is an essential idea for comprehending the network interaction and behaviour of the financial assets. One of the tools that can be used to create and generate this financial network is by using R. R is one of the most used programming languages for statistical computing and graphics. Nevertheless, generating appealing network visualisations using R for publication in academic papers or presentations can be challenging. Two common problems with R: 1) the difficulty to visualise the correlation that involves a large number of companies and 2) the lack of network creation customization in R. This issue however can be resolved using the Gephi software. The primary objective of this paper is to improve the visualisation of financial networks using Gephi software. A better visualization can assist the market participant with the portfolio selection strategy.